Atomically Precise Bimetallic Nanoclusters as Photosensitizers in Photoelectrochemical Cells. Issue 18 (1st March 2019) - Wang, Yu; Liu, Xiao‐He; Kovalenko, Sergey A.; Chen, Qing‐Yun; Pinna, Nicola
Abstract: The atomically precise bimetallic nanocluster (NC), Au24 Ag20 (PhCC)20 (SPy)4 Cl2 (1 ) (Py=pyridine), was employed for the first time as a stable photosensitizer for photoelectrochemical applications. The sensitization of TiO2 nanotube arrays (TNA) with1 greatly enhances the light‐harvesting ability of the composite because1 shows a high molar extinction coefficient ( ϵ ) in the UV/Vis region. Compared to a more standard Au25 (SG)18 ‐TNA (2 ‐TNA; SG=glutathione) composite, 1 ‐TNA shows a much better stability under illumination in both neutral and basic conditions. The precise composition of the photosensitizers enables a direct comparison of the sensitization ability between1 and2 . With the same cluster loading, the photocurrent produced by1 ‐TNA is 15 times larger than that of2 ‐TNA. The superior performance of1 ‐TNA over2 ‐TNA is attributed not only to the higher light absorption ability of1 but also to the higher charge‐separation efficiency. Besides, a ligand effect on the stability of the photoelectrode and charge‐transfer between the NCs and the semiconductor is revealed. This work paves the way to study the role of metal nanoclusters as photosensitizers at the atomic level, which is essential for the design of better material for light energy conversion. Abstract : Soak up the sunlight : The precise composition of metal nanoclusters enables the study of their roles as photosensitizers in photoelectrochemical cells at the atomic level.